2004
DOI: 10.1158/0008-5472.can-04-0986
|View full text |Cite
|
Sign up to set email alerts
|

Microregional Effects of Gemcitabine in HCT-116 Xenografts

Abstract: To examine the tumor microregional effects after gemcitabine administration to mice, we mapped the location of proliferating and hypoxic cells relative to vasculature in human colon cancer xenografts. The S-phase marker bromodeoxyuridine was used as a surrogate of drug effect and administered 2 hours before tumor excision, whereas vessel position and perfusion were assessed via staining for CD31 and intravenous injection of carbocyanine, respectively. Hypoxia was detected using pimonidazole. Images of the four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
69
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 11 publications
2
69
0
Order By: Relevance
“…7) that are well below the previously reported peak plasma concentration (100 Amol/L) of gemcitabine at the maximum tolerated dose (17). These results suggest that following a metronomic schedule, gemcitabine may have an antitumor effect.…”
Section: Discussionsupporting
confidence: 48%
“…7) that are well below the previously reported peak plasma concentration (100 Amol/L) of gemcitabine at the maximum tolerated dose (17). These results suggest that following a metronomic schedule, gemcitabine may have an antitumor effect.…”
Section: Discussionsupporting
confidence: 48%
“…HT29 tumor xenografts have been characterized as having a more mature vascular phenotype as compared with the HCT116 model in terms of collagen and smooth muscle actin association with blood vessels (28). The two tumor types have been previously used to model drug penetration and were selected as they exhibited clearly demarcated regions under the influence of individual vessels and hence allowed for clearer interpretation of the interplay between microregional drug delivery and activity (29)(30)(31)(32). In addition to the tumor-based studies, an in vitro 3D tissue disk assay was used.…”
Section: Introductionmentioning
confidence: 99%
“…Repopulation of tumor cells following radiotherapy is well documented but repopulation following chemotherapy has not been studied extensively. Limited studies have found that the rate of proliferation of surviving tumor cells may increase following chemotherapy (19)(20)(21)(22). The objectives of the present study Reoxygenation and repopulation at 24 hours in PC-3 tumors treated with pimonidazole and: saline (control; black), docetaxel (8 mg/kg; blue), TH-302 (150 mg/kg; purple) or combination (orange).…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, we found that combined treatment inhibited proliferation in the reoxygenated compartment-an important finding as it provides support for the activation of TH-302 in hypoxic tissues and its ability to reduce repopulation from this region. Huxham and colleagues reported that gemcitabine treatment of HCT-116 tumors induced proliferation of cells located at the border of necrotic (presumably hypoxic) regions (19). Fung and colleagues also reported that cell proliferation (repopulation) occurred in regions close to hypoxia following chemotherapy (3).…”
Section: Discussionmentioning
confidence: 99%